2015
DOI: 10.5929/2015.5.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Women in Business: Influences on the Undergraduate Major Choices

Abstract: This study employs a survey of undergraduate business school freshmen to examine factors that influence their decision to study business and whether these factors differ by gender. Specifically, the study examines internal factors, such as students' perceived aptitudes and interests in the subject; external factors, such as compensation and job availability; and social/interpersonal influences, such as input of teachers, school counselors, parents, and friends. This paper follows up on the authors' earlier wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…A plethora of literature exists that examines gender in relation to business education, and includes gender composition in business programs (both students and faculty; Rosenberry, 2016), gender in business curriculum (Valcour, 2013), gendered decision-making and power within business schools (Johnson et al, 2015), and various metrics of success in business schools including enrolment (Trussel & Burke-Smalley, 2018), completion and retention (Cox et al, 2005), programs of study (Geyfman et al, 2015), grades and assessment (Griffith, 2014), and teaching practices (Boehmer & Wood, 2017). Yet a review of the research will demonstrate that the vast majority of literature that considers gender in relation to business education assumes a binary and heteronormative understanding of gender.…”
Section: Gender and Business Educationmentioning
confidence: 99%
“…A plethora of literature exists that examines gender in relation to business education, and includes gender composition in business programs (both students and faculty; Rosenberry, 2016), gender in business curriculum (Valcour, 2013), gendered decision-making and power within business schools (Johnson et al, 2015), and various metrics of success in business schools including enrolment (Trussel & Burke-Smalley, 2018), completion and retention (Cox et al, 2005), programs of study (Geyfman et al, 2015), grades and assessment (Griffith, 2014), and teaching practices (Boehmer & Wood, 2017). Yet a review of the research will demonstrate that the vast majority of literature that considers gender in relation to business education assumes a binary and heteronormative understanding of gender.…”
Section: Gender and Business Educationmentioning
confidence: 99%
“…The types of instructional technology and media experiences they receive during their college years are dependent on their chosen majors and their professors' technology preferences. The major they select is influenced by various factors, such as confidence, current skill levels, personal aspirations, degree of difficulty, expected financial returns, family expectations, social norms, and college offerings (Geyfman, Force, & Davis, 2015;Monaghan & Jang, 2017). These are all important factors to consider when designing an undergraduate education course about how to incorporate technology and media into classrooms.…”
Section: Integrating Technology and Arts-based Inquiry Into Classroomsmentioning
confidence: 99%
“…Over the last two decades, many studies have queried women about their interest in technology-related disciplines using surveys, focus groups, and direct interviews (Beyer, 2008(Beyer, , 2014Buschor, Berweger, Frei, & Kappler, 2014;Cory, Parzinger, & Reeves, 2006;Geyfman, Force, & Davis, 2016;Joshi & Schmidt, 2006;Merhout, Havelka, & Rajkumar, 2016;Stout, Grunberg, & Ito, 2016;Wang et al, 2015;Zhang, 2007). These studies have found that parental influence, role models, stereotypes, knowledge of the field, influence of peers, self-efficacy, and external encouragement are important factors that affect women's interest in IS.…”
Section: Figure 1 Percent Of Female Employees At Selected Technologymentioning
confidence: 99%
“… Low self-efficacy and low confidence in their personal knowledge and abilities in technology. This point is hardly limited to IS; women display less confidence in their knowledge and abilities in general (Beyer, 2014;DuBow & James-Hawkins, 2016;Geyfman et al, 2016;Jung, Clark, Patterson, & Pence, 2017;Sax et al, 2017).  Concern about the level of difficulty and workload associated with technology-related majors (Jung et al, 2017;Pappas et al, 2016).…”
mentioning
confidence: 99%